Exploring the stakeholders who should be involved in the introduction and implementation of system-wide change processes: A case study of the Nigerian basic education system - P. B., Oloba (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
Stakeholders’ involvement is essential for the successful implementation of any educational innovations, and for a new educational system to succeed, all stakeholders must be part of the process. Research has shown that one of the reasons why educational reforms in Nigeria have not been effectively implemented is as a result of a lack of stakeholder involvement, as the government alone cannot successfully shoulder the responsibility of education reform. For that reason, the aim of this study is to explore the stakeholders that should be involved in the introduction and implementation of system-wide change processes in the Nigerian basic education system. Through the lens of a constructivist research paradigm, the study is located in a generic qualitative research design with the use of one-on-one semi-structured interviews with 38 participants from 12 stakeholder groups for the data collection and the use of qualitative content analysis techniques for analysing the data. The findings of the study present the political class, teachers, reform facilitators, proprietors of private schools, students, parents, the legislature, the government, traditional rulers, religious leaders, NGOs, teacher training institutions, the Nigerian union of teachers, and the ministry of education as the stakeholders that should be involved in educational reform. For the future introduction and implementation of educational change in the Nigerian basic school system to be effective, it is recommended that all stakeholders in education be adequately involved throughout the change effort, from the planning stage to the implementation stage to the evaluation stage.